AKUNTABILITAS MANAJEMEN KINERJA SATUAN PENDIDIKAN KECAKAPAN HIDUP BERBASIS BUDAYA LOKAL : Studi Tentang Pengaruh Perencanaan, Kepemimpinan, dan Iklim Organisasi Terhadap Kinerja Satuan Pendidikan Pelaksana Program Pendidikan Kecakapan Hidup di Provinsi Jambi - Ramatni, Ali (2010)
THE ACCOUNTABILITY OF PERFORMANCE OF LOCAL CULTUR-BASED LIFE SKILL EDUCATION UNITS (A Study on the Influence of Planning, Leadership, and Organization Climate towards the Performance of the Administration of Life skill Education Program in the Province of Jambi), A Dissertation, Bandung, School of PostGraduate Studies, Indonesia University of Education, 2010. This research was based on the notion that life skill education as one of the superior programs of informal education played a strategic role in preparing adult learners with life skills appropriate with market needs, in order for them to compete with other nations. On the other hand, the life skills program in the Province of Jambi had not been managed optimally. The condition reflected performance problem of the life skill education. The main problem of this research was formulated as follow: How do the educational planning, educational leadership, and organizational climate influence to wards and mean for the performance of life skills education unit in the Province of Jambi? This research employed the approaches of descriptive and explanatory surveys. The objects of this research were life skills education unit, consisting of training and course Institutions, life skills Education in Cooperation with Vocational School/Polytechnics, Rural-Oriented Life Skills Education, and City-Oriented Life skills Education. The respondents were 41 life skills education unit in the at 48 subjects for the respondents of this research were obtained. The data were gathered through close-ended questionnaire, revealing the point of views of the respondents on the four variables tested. The data analysis used path analysis technique processed with computer aid. The results of this research showed that as a whole, the variable of life skills education contributed positively and significantly toward the variable of life skills education performance simultaneously as much as 93.70%, contributed by educational planning (X1) as much as 15,37%; educational leadership (X2) as much as 37,09%; and educational organizational climate (X3) as much as 10,18%. The findings of this research imply that the human resources, infrastructures, and facilities are required to be appropriate in terms of number and quality. In line with tha, it will be better if life skills education program planning give emphasis on the graduates, preparation to master certain skills necessary for their lives. In the implementation of hypothetical model, the performance management life skills education units is recuired to be committed to the continuous maintenance and improvement of the learning characteristics, education, professionalism, adult learners' participation, and the society's initiatives. What is similarly important is the appropriate understanding on the organizational vision and life skills education vision, and the willingness for self-development in the contect of learners' organization.